Analisis Kerentanan dan Pemetaaan Stakeholders di Kecamatan Pomalaa Kabupaten Kolaka: (Kajian Pemetaan Sosial di Wilayah Operasional PT Antam UBPN Sulawesi Tenggara) - Abdul Sabaruddin; Nursamsir; Taslim Fait; Maulid; Sudirman Baso (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
The purpose of this study is to identify vulnerable community groups and map the interests of stakeholders in the area of operation of PT Antan Tbk UBPN Sultra. This study was conducted in Pomalaa District, through a mixed method approach that combines quantitative data analysis methods. Because this study uses a mixed method approach, the informant is used as a source of data in a qualitative approach. The determination of informants is done by snowball sampling method. Meanwhile, the probability sampling technique is used for the quantitative approach. Proportional cluster sampling is a form of probability sampling that is used, and the way it works is by identifying in advance the groups that represent the population. Information collected through the results of field research, both primary data and secondary data. The results show that the vulnerable groups in the company's operational areas were pre-prosperous families (poor families), the elderly, people with disabilities, and the mentally handicapped (physical, speech and hearing impaired, mental, and blind). Pre-prosperous families (poor families) are the highest vulnerable group, reaching 2,152 people out of 30,680 residents of Pomalaa Subdistrict. Meanwhile, stakeholders that influence the success of company programs in Pomalaa Subdistrict are the village head, village secretary, head of Bumdes, traditional leaders, women leaders, religious leaders (Islamic and Christian), and community leaders.